Ontology Enriched Framework for Cloud-based Enterprise Interoperability - Jardim-Goncalves, R.; Cretan, A.; Coutinho, C.; Dutra, M.; Ghodous, P. (Concurrent Engineering Approaches for Sustainable Product Development in a Multi-Disciplinary Environment, 2012)
The globalised world has entered the service era, where an enterprise is connected to the entire world, producing and consuming services using the internet. Virtualisation and service provisioning are paradigms that rule the interoperation of the world today. However, this interoperability mostly relies on a set of agreed message syntax exchanges, agreements that are fragile and limited in their scope, and it lacks a proper framework that can manage the sustainability of a networked Enterprise Interoperability (EI) environment. After presenting the problem and the research questions concerned with cloud-based EI, the paper presents the actual practices and research challenges on EI identified needs, addressing ontology, negotiation and cloud-based aspects for sustainability in EI. Then it proposes an ontology-enriched framework for cloud-based EI, and discusses on its validation in an industrial scenario.